Polygonatum sibiricum polysaccharide prevents depression-like behaviors by reducing oxidative stress, inflammation, and cellular and synaptic damage - Shen, Fengming; Song, Zhujin; Xie, Pan; Li, Lei; Wang, Bin; Peng, Daiyin; Zhu, Guoqi (Journal of ethnopharmacology, 2021)
According to traditional Chinese medicine (TCM) theory (Yi Xue Zheng Zhuan), the main factors associated with the pathogenesis of depression are deficiencies relating to five zang organs, Qi, and blood. Polygonatum sibiricum F. Delaroche (PS), which may avert these pathological changes, has been used in a variety of formulas to treat depression. However, the effects and mechanism of action of PS, alone, and especially those of its main active component PS polysaccharide (PSP), on depression remain unexplored. To determine the effects of PSP on depression-like behaviors and to elucidate its mechanism of action. PSP was isolated from dried PS rhizomes and qualified using transmission electron microscopy and Fourier transform infrared spectroscopy. Lipopolysaccharide (LPS) and chronic unpredictable mild stress (CUMS)-induced depression models were used to evaluate the antidepressive effects of PSP. Veinal blood and brain tissue were collected to determine the levels of hippocampal 5-HT, serum cortisol (CORT), brain and serum cytokines, and hippocampal oxidation-related indicators. The protein expression levels of phosphorylated extracellular signal-regulated kinase (p-ERK1/2), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), glial fibrillary acidic protein (GFAP), phosphorylated protein kinase B (p-Akt), phosphorylation of the mammalian target of rapamycin (mTOR), caspase-3, GluA1 and GluA2, and GluN2A and GluN2B were determined using western blotting and immunofluorescence. Nissl staining was performed to detect histopathological changes in brain tissues. Injection of LPS (i.p.) induced depression-like behaviors, reduced the level of hippocampal 5-HT, increased the serum CORT level and hippocampal oxidative stress (ROS), and prompted the activation of ERK1/2, NF-κB, and GFAP and an inflammatory response. Conversely, PSP administration reduced these changes and prevented depression-like behaviors. PSP administration also promoted hippocampal expression of p-Akt, p-mTOR, GluA1, and GluA2; reduced the expression of caspase-3, GluN2A, and GluN2B; and prohibited the loss of granular cells in the DG region. These results indicate that PSP prevents depression-like behaviors, and synaptic and neuronal damage probably by reducing ROS/HPA axis hyperfunction and the inflammatory response. [Display omitted]